Trail running through the woods. - Unknown:::Creator::::::::::::
Photograph shows a trail running through the woods at the YWCA's Camp Ayun Mapu in Big Basin. Part of the trail is a wooded walk with a railing, and there is a bridge on the far left of the photograph.